Latent infection of Mycobacterium tuberculosis among nursing students from a public university - Daniela Furtado Rodrigues de Andrade; Maria do Rosário Conceição Moura Nunes Nunes; Carolina Bezerra Valadares; Hugo Leonardo Barros de Arêa Leão; Francisco de Moura Bezerra Filho; Viriato Campelo (Universidade de Santa Cruz do Sul, 2018)
Background and Objectives: To analyze the prevalence of M. tuberculosis Latent Infection (ILTB) among nursing students of a public higher education school. The study contributes to a better understanding of occupational tuberculosis and to the improvement of strategies for the prevention and monitoring of tuberculosis. Methods: A descriptive cross-sectional study, conducted in Teresina-PI. Was used a socio-educational and epidemiological characterization questionnaire and, after filling in, the participants (n = 63) underwent tuberculin skin test using the intraday method. Results: The prevalence of ILTB was 36% and the factors associated with ILTB were the semester, hospital placements and contact with patients in isolation. Conclusion: The results point to the high prevalence of ILTB in nursing students and reinforce the importance of the tuberculin test as a way to monitor ILTB in this population.